Clinical reasoning in musculoskeletal practice: students' conceptualizations. - Hendrick P; Bond C; Duncan E; Hale L (Physical Therapy, 2009)
BACKGROUND: Qualitative research on physical therapist students' conceptualizations of clinical reasoning (CR) is sparse. OBJECTIVES: The purpose of this study was to explore CR from students' perspectives. DESIGN: For this study, a qualitative, cross-sectional design was used. METHODS: Thirty-one students were randomly selected from years 2, 3, and 4 of an undergraduate physical therapist program in New Zealand. Students were interviewed about their understanding of CR and how they used it in practice in a recent musculoskeletal placement. Interviews were recorded and transcribed verbatim. A 3-stage analysis included the categorization of students' conceptualizations on the basis of the meaning and the structure of each experience and the identification of cross-category themes. RESULTS: Five qualitatively different categories were identified: A--applying knowledge and experience to the problem, patient, or situation; B--analyzing and reanalyzing to deduce the problem and treatment; C--rationalizing or justifying what and why; D-combining knowledge to reach a conclusion; and E--problem solving and pattern building. Cross-category analysis revealed 5 general themes: forms of CR, spatiotemporal aspects, the degree of focus on the patient, attributions of confidence, and the role of clinical experience. CONCLUSIONS: Categories formed a continuum of CR from less to more sophistication and complexity. Students were distributed evenly across categories, except for category E, which included only students from years 3 and 4. Each category comprised a logical, coherent experiential field. The general themes as critical dimensions suggest a new way of exploring CR and suggest a possible pathway of development, but further research is required. These findings have implications for teaching and the development of physical therapy curricula.